EFL learners’ major problems in writing argumentative essays in the IELTS test: Insights from a Vietnamese context : - Lê, Bích Thuận (Đại học Cần Thơ, 2011)
This thesis reports on a research study in the field of academic writing in the Mekong Delta region of Vietnam. The study investigated EFL learners’ major problems in writing argumentative essays and the causes correlated with these problems in the IELTS test – Academic module